Potential Neuroprotective Effect of Trimetazidine and Metformin on Autophagy in a Rat Model of Diabetic Peripheral Neuropathy: Role of LC3 and P62 - Doaa Genedy, Abdel-Motaal M. Fouda, Ahlam Elmasry Heba Hany, Samah fouad, Ahmed Abdel-monem Elmetwally (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Diabetic peripheral neuropathy (DPN), a common complication of diabetesmellitus. Currently, no specific etiology treatment has been established promoting a keeninvestigation into the underlying mechanism and potential strategies in the medical field. Thisstudy tested the potential protective effect of trimetazidine or metformin each of them aloneor combined on autophagy in a rat model of diabetic peripheral neuropathy